A neoliberal framework for urban housing development in the Global South - Chisumbe, Sampa; Aigbavboa, Clinton Ohis; Mwanaumo, Erastus; Thwala, Wellington Didibhuku (Emerald Publishing Limited, 2024)
Cities in developing countries are faced with housing challenges that differ from country to country. The reasons for and the nature of these challenges differ. For cities in sub-Saharan African countries, many residents live in unplanned settlements. As a result, most residents lack decent housing as well as access to basic services. This is due to, among other factors, ineffective urban planning, weak urban governance, low private sector involvement, and lack of access to affordable housing finance - yet few empirical studies have investigated and developed frameworks aimed at improving urban housing. A Neoliberal Framework for Urban Housing Development in the Global South highlights the factors which predict urban housing development from developing countries'perspective, providing a guide for countries in the sub-Sahara, where governments have limited financial resources competing among several needs. Anchored on neoliberalism, it argues that urban housing development is an eight-factor construct consisting of legal framework, tenure, stakeholder coordination, stakeholder participation, stakeholder capacity, adaptive housing regulations, housing finance, and governance. The authors outline the role of the state in creating an enabling environment for other stakeholders to participate in the provision of affordable housing for all.